Granular cell tumor of the esophagus in an adolescent - Ji Sun Lee; Kyung Ok Ko; Jae Woo Lim; Eun Jeong Cheon; Young Jin Kim; Jang Sin Son; Jung Min Yoon (Korean Pediatric Society, 2016)
Esophageal granular cell tumor (GCT) is a rare neoplasm originating from the Schwann cells of the submucosal neuronal plexus. Histology is the gold standard for its diagnosis. Endoscopic resection or surgical excision should be considered, depending on the potential for malignancy. Here, we report a case of an esophageal GCT in an adolescent. A 12-year-old boy presented with a 1-year history of dysphagia and vomiting. Upper gastrointestinal endoscopic examination and esophagography showed narrowing of the midesophagus, and computed tomography angiography of the thoracic aorta revealed an esophageal or periesophageal mass posterior to the paratracheal segment of the esophagus. The tumor was surgically excised, and based on the pathological findings, esophageal GCT was diagnosed.